2022
DOI: 10.3390/ijms23105495
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Seed Germination under Low-Temperature Stress in Maize

Abstract: Low-temperature stress delays seed germination in maize. Different maize inbred lines display various low-temperature resistance, but the dynamic changes in seed germination under low-temperature stress in maize remain unknown, especially at the transcriptome level. In this study, low-temperature-resistant maize (RM) inbred line 04Qun0522-1-1 had a significantly faster germination speed than low-temperature-sensitive maize (SM) line B283-1 under low-temperature stress. Moreover, the total antioxidant capacity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…In general, cold stress can induce membrane lipid peroxidation in plants and produce the accumulation of membrane lipid peroxidation, MDA, which is directly proportional to the stress time and inversely proportional to the temperature [38]. In this study, there was a significant increase in MDA in different broccoli genotypes at the seedling stage compared to that in the control after cold stress, which is consistent with some previous research [39].…”
Section: Discussionsupporting
confidence: 92%
“…In general, cold stress can induce membrane lipid peroxidation in plants and produce the accumulation of membrane lipid peroxidation, MDA, which is directly proportional to the stress time and inversely proportional to the temperature [38]. In this study, there was a significant increase in MDA in different broccoli genotypes at the seedling stage compared to that in the control after cold stress, which is consistent with some previous research [39].…”
Section: Discussionsupporting
confidence: 92%
“…Low temperature stress can affect a series of morphological and physiological changes of plants, and delay seed germination of maize, which has a great impact on its growth, yield and quality [ 38 ]. LT stress can increase the accumulation of reactive oxygen species (ROS), and the ROS scavenging enzymes in plants are mainly antioxidant enzymes, such as SOD, POD and CAT, etc [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomes are indispensable components of cells that translate mRNA into functional proteins [11]. Endogenous signals and environmental stimuli, such as ambient temperature, can regulate ribosome biosynthesis [12][13][14]. Previous studies have identified that low temperature rapidly inhibits ribosomal biogenesis [15].…”
Section: Introductionmentioning
confidence: 99%